2021
DOI: 10.3390/pr9030555
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Dynamics on a Wettability Patterned Surface during Spray Impact

Abstract: Wettability patterning of a surface is a passive method to manipulate the flow and heat transport mechanism in many physical processes and industrial applications. This paper proposes a rational wettability pattern comprised of multiple superhydrophilic wedges on a superhydrophobic background, which can continuously remove the impacted spray droplets from the horizontal surface. We observed that the spray droplets falling on the superhydrophilic wedge region spread and form a thin liquid film, which is passive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…A wettability patterned surface (Figure 12i) can benefit from hydrophilicity and hydrophobicity, potentially improving spray cooling performance. Thomas et al 285 recently investigated droplet dynamics on such a patterned wettability surface during spray impact. Atmospheric Water Harvesting.…”
Section: ■ Applicationsmentioning
confidence: 99%
“…A wettability patterned surface (Figure 12i) can benefit from hydrophilicity and hydrophobicity, potentially improving spray cooling performance. Thomas et al 285 recently investigated droplet dynamics on such a patterned wettability surface during spray impact. Atmospheric Water Harvesting.…”
Section: ■ Applicationsmentioning
confidence: 99%
“…(iv) Droplet transport during spray impact on a horizontal surface. Reproduced with permission from ref . Copyright 2021 MDPI under the terms of the Creative Commons CC BY license [].…”
Section: Applicationsmentioning
confidence: 99%
“…A wettability patterned design for heat transfer applications using an array of spray nozzles was patented by Joshi and Dede. 295 Thomas et al 296 demonstrated the transport of liquid on a horizontal, wettability patterned metal surface upon high-speed spray impact (see schematic in Figure 22iv). The metal surface featured several superhydrophilic wedge tracks laid on a superhydrophobic background.…”
Section: Energy and Water Conservationmentioning
confidence: 99%
“…[ 23–33 ] However, these biphilic surfaces often involve complex geometries requiring precisely geometries design, multiple fabrication steps, and sophisticated equipment that make scaling up difficult and expensive. [ 34–37 ]…”
Section: Introductionmentioning
confidence: 99%